Perilestes jueni (Zygoptera: Perilestidae), new species from Amazonas State, Northern Brazil - Mendoza-Penagos, Cristian Camilo; Gonçalves, Myckey Kenzy E Silva; Vilela, Diogo Silva (Zootaxa, 2022)
Perilestes jueni sp. nov. (Brazil, Amazonas State, São Gabriel da Cachoeira, Ponto 8 (0.165, -67.007, 92 m asl), 2.xii.2021, C.C. Mendoza-Penagos M. Silva-Gonçalves & S. Da Silva Ribeiro leg.) is described based on one male collected in a remote area of the Brazilian Amazon Forest. The new species is separated from congeners based on cercus morphology.